Coexistence and Social Exclusion of Venezuelan Migrants in Lima, Perú: A Psychosocial Approach - Rosa M. Cueto; Liz S. Ayma; César A. Llanco; Fiorella Acedo; Camila Loli (Psychology in Russia: State of Art)
Background. An understanding of the dynamics of intergroup relations, particularly in relation to migrant populations, is of critical importance in a variety of societal contexts. This study examines the relationship between conservatism (Social Dominance Orientation, SDO), intergroup dynamics (stereotypes and intergroup emotions), and social distance (openness to coexistence and tendencies toward exclusion) within the Venezuelan migrant population residing in Lima Metropolitana. Objective. The objective of this study was to investigate the relationships between conservatism, intergroup dynamics, and social distance among Venezuelan migrants in Lima Metropolitana. A sample of 395 residents was utilized for this study. Design. The study employed a correlational research design to examine the relationships between the variables of interest. Correlation analyses were conducted to assess the associations between variables. Path analysis was utilized to explore the underlying mechanisms. Furthermore, group comparisons were conducted to examine differences in attitudes and perceptions across various demographic groups. Results. The findings indicated that there were significant associations across conservatism, intergroup emotions (both negative and positive), stereotypes, and the tendencies toward exclusion and coexistence. Notably, younger participants exhibited more inclusive ideological and intergroup indicators. Moreover, the path analysis demonstrated the pivotal influence of the morality stereotype and ideological dimensions on the integration and exclusion of migrants. Conclusion. The study highlights the significance of cultivating favorable stereotypical perceptions of migrants and emphasizes the impact of age and ideological factors in creating conducive conditions for migrant integration. A contextual understanding of these results underscores the necessity for inclusive policies and interventions that foster social cohesion and integration within communities that have received migrants.